GARAGE DOOR CONTROLLER - Hedri Ramadhani Miarsa; Jalinas Jalinas, SKom, MM (Jurnal Sistem Komputer, 2001)
Garage door control devices connected using an interface as the means men jabatani to pass or transfer data from the microcomputer to the periphery and vice versa. Computer as the controlling and processing the data or information into and out to the periphery of the data previously received by the interface.Â  Which is an electro mechanical stepper motor that works by changing the electronic pulses into discrete mechanical movements, movements of the stepper motor can be arranged ie clockwise or counterclockwise dandapat applied to various kinds perngkat or peripherals such as diskÂ  drives, hard disk cutter.